THE IMPACT OF INNOVATIVE TECHNOLOGIES ON THE STABLE DEVELOPMENT OF ENTERPRISES OF HOTEL INDUSTRY - O. Solntseva; A. Oganesyan (Вестник университета)
Currently, there is increased competition in the hospitality industry and innovative technologies have a direct impact on the sustainable development of enterprises. The article examines the main trends in the development of the hotel industry, particular attention is paid to the conversion of the number of rooms and the provision of various services in the hospitality industry. The impact of innovation on technological processes is analyzed, the analysis revealed the potential benefits of the functioning of the hotel enterprises. Future opportunities for the development of hotels using creative and innovative solutions are discussed. In the review of international hotel complexes the authors come to the conclusion that innovation processes are considered an integral part of modern business in the hospitality industry.